Pathological response analysis of breast cancer in patients submitted to neoadjuvant therapy in a private clinic of Cascavel/PR (Research, Society and Development, 2021)
The present study aimed to analyze the clinical-pathological profile of patients diagnosed with breast cancer and treated with neoadjuvant chemotherapy at COOP from July 2014 to July 2019. Neoadjuvant therapies have the purpose of reduce the tumor burden and improving the pathological complete response (pCR) in patients with advanced tumors and conserving the breast in initial tumors. The pathological response is a way to evaluate the effectiveness of this modality of treatment, as well as the benefits brought by it. The study in question made a quantitative, qualitative and descriptive analysis, in a retrograde way, using physical records from COOP. The conclusion is that there is a statistical association of patients who achieved pCR with younger age, higher levels of Ki-67, absense of estrogen and progesterone hormonal receptor and presence of HER-2 receptor. Therefore, this treatment modality should be considered in patients with a similar profile to obtain a better clinical outcome.